2004
DOI: 10.1542/peds.113.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Child Vulnerability Among Mothers of Former Premature Infants

Abstract: Higher PPCV is associated with worse developmental outcome in premature infants at 1-year adjusted age. Maternal anxiety at neonatal discharge predicts later high PPCV. Interventions to prevent or decrease PPCV in premature infants should be targeted at parents who are more anxious at hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
1
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 29 publications
7
121
1
10
Order By: Relevance
“…Parents of preterm infants have been noted to perceive their infants as medically vulnerable, even in the absence of indicators of medical vulnerabilities. [34][35][36] High parental perception of child vulnerability is associated with high health-care utilization along with an increased risk of behavior problems and altered parent-child interaction. [37][38][39][40] One recent study of preterm infants suggested that higher parental perception of child vulnerability is correlated with worse developmental outcomes at 1 year adjusted age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of preterm infants have been noted to perceive their infants as medically vulnerable, even in the absence of indicators of medical vulnerabilities. [34][35][36] High parental perception of child vulnerability is associated with high health-care utilization along with an increased risk of behavior problems and altered parent-child interaction. [37][38][39][40] One recent study of preterm infants suggested that higher parental perception of child vulnerability is correlated with worse developmental outcomes at 1 year adjusted age.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] One recent study of preterm infants suggested that higher parental perception of child vulnerability is correlated with worse developmental outcomes at 1 year adjusted age. 34 Pediatricians need to be alert to parental anxiety and provide support and reassurance to these families. Understanding more about how to optimize care and lessen anxiety through the transition from the NICU to the home may diminish the risk of the vulnerable child syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…28 En la población de niños con antecedentes de prematurez, varias publicaciones alertan acerca de la importancia de la detección temprana de este síndrome. 29,30 A través de las representaciones sociales analizadas en torno al cuerpo y la escolaridad, observamos la capacidad de los pacientes para resignificar los estigmas generados por la prematurez. En este sentido, una fortaleza de la metodología utilizada es que generó un espacio de diálogo e identificación donde se expresaron angustias personales, se intercambiaron consejos, se problematizó lo que se consideraba anormal socialmente y se destacaron las fortalezas propias y de los otros.…”
Section: Discussionunclassified
“…8,12 Factors such as high level of family stress, low maternal responsiveness, and impaired parental competence, seem to play a direct role in children s development. 13 There are two types of support to parents of risk newborns in the NICU: formal support, provided by some healthcare workers, and informal support, provided by the family and friends. 14 The literature highlights the role of healthcare workers in mobilizing and strengthening family resources by implementing support groups, as a way to organize the work in the NICU, meeting the needs of newborn infants, and giving parents the opportunity to deal with the birth of their child and to cope with his/her hospitalization.…”
Section: Birth and Nicu Admission After Hospital Dischargementioning
confidence: 99%